2023
DOI: 10.3390/axioms12100982
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Explicit Finite Difference Method and Physics-Informed Neural Networks for Solving the Burgers’ Equation

Svetislav Savović,
Miloš Ivanović,
Rui Min

Abstract: The Burgers’ equation is solved using the explicit finite difference method (EFDM) and physics-informed neural networks (PINN). We compare our numerical results, obtained using the EFDM and PINN for three test problems with various initial conditions and Dirichlet boundary conditions, with the analytical solutions, and, while both approaches yield very good agreement, the EFDM results are more closely aligned with the analytical solutions. Since there is good agreement between all of the numerical findings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Based on the one-dimensional dual-cover system, our method adopts a PUM-like technique to connect PCs, and there is no requirement for MC mesh shapes. (6) Various initial-boundary value problems are considered in Section 6, including trigonometric functions, polynomial functions, particular traveling solutions and the Riemann problem with two constant initial values. Numerical evidence underscores that the results of the ENMCGM are in concordance with analytical solutions and the published results for the Burgers' equation, particularly for high Reynolds numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the one-dimensional dual-cover system, our method adopts a PUM-like technique to connect PCs, and there is no requirement for MC mesh shapes. (6) Various initial-boundary value problems are considered in Section 6, including trigonometric functions, polynomial functions, particular traveling solutions and the Riemann problem with two constant initial values. Numerical evidence underscores that the results of the ENMCGM are in concordance with analytical solutions and the published results for the Burgers' equation, particularly for high Reynolds numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been dedicated to designing accurate and stable computing schemes to solve Burger's equation for large Reynolds numbers. According to the manner for spacial discretization, these schemes can be roughly categorized into mesh-based approaches [2][3][4][5][6][7][8] and mesh-free methods [9,10]. However, mesh-based approaches, such as finite difference/volume/element methods, seriously rely on deliberated meshes to discretize problem domain onto grid lines or elements to acquire accurate spacial approximation.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed how wall design and orientation can optimize the thermal comfort of a building. Our next work will simulate the windows and the roof and we will use ANNs to solve the transient PDE itself, similarly to the work [43].…”
Section: Discussionmentioning
confidence: 99%
“…Guided by physical loss terms, PINN requires fewer or no paired input-output observations to be trained and provides better generalization. The application of PINN has expanded to various fields, including fluid mechanics [20], biomedicine [21], materials science [22], fracture mechanics [23], power systems [24], and scientific machine learning (SciML) [25]. Therefore, PINN is a highly promising technique for addressing the issue of displacement reconstruction.…”
Section: Introductionmentioning
confidence: 99%